Universal Screening for Social Needs in a Primary Care Clinic: A Quality Improvement Approach Using the Your Current Life Situation Survey - Sundar, Kumara Raja (Perm J, 2018)
CONTEXT: Kaiser Permanente’s Care Management Institute created a screening tool, Your Current Life Situation (YCLS), which primarily is used to identify social needs for populations at risk of high health care utilization. OBJECTIVE: This frontline improvement project was designed to address key stakeholder concerns about implementing universal screening for social needs using the YCLS in a primary care clinic. METHODS: I conducted a rapid stakeholder analysis through informal conversations to identify the most important concerns. Four Plan-Do-Study-Act cycles were conducted to answer stakeholder questions and address concerns. RESULTS: Stakeholders expressed concerns including YCLS length and low screening acceptability and the possibility that too few or too many patients may have social needs. Throughout the project’s duration, 125 office visits occurred and 111 patients were screened. Among the patients for whom findings were positive, 27% requested help. Of the 14 patients who were not screened, only 1 patient opted out of screening. Practitioners and medical assistants stated that administration of the YCLS screening tool did not disrupt clinic workflow. CONCLUSION: By using a frontline improvement approach, these investigators could answer questions and address concerns most important to local operational stakeholders when implementing screening for social needs. When practitioners conduct universal social needs screening and more fully understand social needs prevalence in a primary care clinic, resources can be tailored more effectively to accommodate patient needs.